Design and construction of a hydrofluidization system. Study of the heat transfer on a stationary sphere - Peralta, Juan Manuel (2009)
In chilling and/or freezing of foods by hydrofluidization (HF), the liquid refrigerant is pumped through orifices or nozzles, creating agitating jets. The objectives of this work were to design and build a HF system of pilot scale and to study the heat transfer on a stationary copper sphere impinged by a liquid jet generated by the HF system. Parameters from the literature were taken into account for the HF system construction. Measurements of surface heat transfer coefficients in the HF system were carried out using a solution of NaCl-water as refrigerant. Copper spheres of different diameters (D) and co-linearly placed in front of a round jet generated by a 3-mm (d) diameter orifice were used. Re, Pr, the orifice-sphere distance (H/d), and the curvature of the sphere surface (d/D) were considered in a correlation for Nusselt number for the HF system. The ranges studied were: 15000 =< Re =< 115000; 9.2 =< Pr =< 11.5; 1.66 =< H/d =< 16.66; 0.15 =< d/D =< 0.30. The HF system constructed is very versatile and it may be easily modified for experimental studies related to chilling and/or freezing of foods by hydrofluidization. Nusselt number range was 70-400, it increased when Re and Pr increased, it had a maximum for 3 < H/d < 10, and it decreased when d/D increased.